The Student's Perception of The Use of Wattpad in Reading Mastery Through Story For Eleventh Students at MA Matholibul Huda Mlonggo in Academic Year 2023 - Sari, Yudith Puspita; Haryanto, Haryanto (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This study analyses the students’ perceptions of using the Wattpad application in reading mastery. It used a qualitative descriptive design with inductive analysis, which uses descriptive data in written or oral words. The researcher used the non-probability sampling technique to get deeper data. The participants are 35 students of the eleventh-grade science class of MA Matholibul Huda Jepara. The researcher used interviews and documentation to collect the data. To analyze the obtained data, the researchers used coding. Researchers compare different codes, and several codes are combined into one because of the emergence of a similarity. The study's results found that the motivation and engagement aspects of learning reading through the Wattpad application highlight the platform's potential to foster a positive reading culture among students. Teachers can better understand how Wattpad influences students' reading habits, interests, and engagement with literature. The improvement in reading aspects provides a comprehensive view of the various dimensions of reading skill improvement. The variety of content in learning reading emphasizes the platform's ability to cater to diverse interests and reading preferences. The positive influence and reading habits for learning reading foster a love for reading and develop consistent reading practices among students. The challenges and negative aspects of learning reading emphasize potential barriers to effective reading engagement and literacy development